Identifying and evaluating antihypertensive and antioxidant capacities of the novel bi-functional peptides isolated from tilapia skin - Xinrun Zhuang; Douyong Min; Hongrui Jiang; Weijian Zeng (Future Foods)
This study aimed to fabricate novel bi-functional peptides with hypertension regulating and antioxidant abilities from tilapia skin. The neutral protease-treated tilapia skin hydrolysate followed by pepsin (TSH9) exhibited the higher performance in DPPH (81.03 ± 0.09 %) and superoxide radical (80.90 ± 0.16 %) scavenging capacities, angiotension converting enzyme inhibitory (ACEI, 86.08 ± 0.26 %) activity, and protection against oxidative damage in HepG2 cells. Fraction I (molecular weight < 1 kDa) obtained by ultrafiltration and gel filtration chromatography from TSH9 showed excellent antihypertensive properties in high and low glucose induced HUVECs models, by enhancing SOD activity, promoting the disproportion of intracellular O2∙−, reducing intercellular ROS levels, and then decreasing oxidative stress. Three novel peptides, GPRGPPGPPGSSGPQG, AGPQGPIGPR, and FGPAGPAGPRGP, were identified by LC-MS/MS and screened by multiple bioinformatic databases. Molecular docking showed that the peptides may interact with the S1 pocket and proton receptor residues of ACE to exhibit antihypertensive properties. Meanwhile, the hydrophobic interactions and hydrogen bonds were found as important forces for the peptide-associated biological activity. These results suggest that the bi-functional peptides with ACEI and antioxidant activities derived from tilapia skin can be promising remedies or ingredients for the development of functional foods and novel therapeutic strategies for hypertension.